The Impacts of Monetary and Fiscal Policies on Gross Domestic Product of China After the Asian Financial Crisis in 1997 - PHANTHASITH, Somsanith; CHANTHAVONE, Thongphanh; HER, Pheng (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
China's economy has been developing rapidly. Since 2010, China has become the world's second largest economy after the United States. The driving force behind the rapid economic growth due to clear economic policy. Therefore, the purpose of this research is to study the effects of monetary and fiscal policies on China's gross domestic product by using Autoregressive Distributed Lag (ARDL) model, which used the time series data from 1998-2000. The results found that it has both short-run and long-run relationship. The ARDL (1 1 2) was used in this study. In the long run, the ratio of M2 and government expenditure has positive relationship to GDP, with statistical significance levels of 0.05 and 0.01 respectively. In the short run, only the ratio of M2 has relationship with GDP at the statistically significant level of 0.01, but it was against theoretically which may be resulted from a small sample size. Considering the coefficients of the short-run Dynamic Error correction, there is a statistically significant level of 0.01. This implies a high speed of adjustment to equilibrium after a shock, approximately 95.7 percent of disequilibria from the previous year’s shock converge back to the long run equilibrium in the current year.